A new modeling framework for networked discrete-event systems. (April 2022) - Tai, Ruochen; Lin, Liyong; Zhu, Yuting; Su, Rong
Abstract: This paper proposes a new framework for modeling networked discrete-event systems (DES) with channel delays and losses. We construct a more elaborated model for the plant G and supervisor S by endowing them with an embedded module to preprocess the received messages and defining state transition mapping and output mapping to model the dynamics of G and S, which could provide users with flexibility to realize different mechanisms, and thus could potentially generate more permissive controllers. Two sets of new formulations are established to capture the temporal relationships between channel inputs and outputs without assuming the first-in-first-out (FIFO) property, which naturally contains the model without delays and losses in the Ramadge–Wonham framework. Based on the defined mappings of each component, the closed-loop behavior is defined to describe the concurrent system dynamics. We hope the new framework could serve as an analysis tool, and possibly the building block for a synthesis tool, for future theoretical explorations and practical implementations of networked DES control.